2006
DOI: 10.1111/j.1445-5994.2006.01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there a risk to safety when working in the New South Wales underground coal‐mining industry while having binaural noise‐induced hearing loss?

Abstract: This study indicates that workers who have lost up to 54% binaural high tone hearing and are older than 29 years do not appear to have an increased risk to safety when compared with workers who do not have hearing loss. However, workers in the young age group of <29 years who have high tone hearing loss may be at an increased risk of accident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Several eligible papers considered more than one health problem, and as a result we identified 19 8,10,15,16,20-23,25,26,31,35-39,41,43,44 papers on hearing problems, 14 papers on visual problems, 8,16,21-23,25,31,35-38,40,43,44 15 papers related to mental health, 11,13,14,17,21,22,28,33,35-38,40,43,44 15 papers related to other health problems (musculoskeletal, cardiovascular, epilepsy, diabetes and allergy and asthma), 8,9,12,15,16,20,23,29,30,35-38,40,42 and 12 papers related to medication. 7,9,18,19,25,27,29,30,31,32,34,40…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several eligible papers considered more than one health problem, and as a result we identified 19 8,10,15,16,20-23,25,26,31,35-39,41,43,44 papers on hearing problems, 14 papers on visual problems, 8,16,21-23,25,31,35-38,40,43,44 15 papers related to mental health, 11,13,14,17,21,22,28,33,35-38,40,43,44 15 papers related to other health problems (musculoskeletal, cardiovascular, epilepsy, diabetes and allergy and asthma), 8,9,12,15,16,20,23,29,30,35-38,40,42 and 12 papers related to medication. 7,9,18,19,25,27,29,30,31,32,34,40…”
Section: Resultsmentioning
confidence: 99%
“…Several studies employed an independent assessment of exposure 10,13,25,39,42 or outcome 18,28,30,31 or both, 12,29,40 but for the most part, exposures and outcome were ascertained by self-report at a single time point. Few of the cross-sectional and retrospective studies established by design that exposure preceded outcome, and we rated the potential for inflationary bias as ‘high’ for at least some comparisons in 14 of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…16 (See also "Special Populations" (pgs. [226][227][228][229] in Part 2, "Addressing the Problem," for a discussion of issues related to non-native speakers of English.) Studies of noise exposures in several other occupations have only just begun.…”
Section: Prevalence Of Noise Exposure In the Workplacementioning
confidence: 99%
“…225 Related studies are described in the literature by Choi et al, 226 who found that hearing loss and the occasional use of hearing protectors were significantly associated with the risk of injury among agricultural workers. In addition, Viljoen et al 227 found that hearing loss did not appear to increase the safety risk for coal miners older than 29 years, but it did increase the risk for younger workers.…”
Section: Communication Safety and Warning Signal Interferencementioning
confidence: 99%
“…[184][185][186] Inability of hearingimpaired workers to hear warning signals is another issue. Several studies have indicated that noise-exposed hearing-impaired workers may be at increased risk for occupational accidents, 187,188 and focus groups conducted among these workers indicated that the workers perceive themselves at increased risk due to their hearing impairment. 189 However, hearing conservation regulations do not take into account the special difficulties encountered by hearing-impaired workers, and most hearing loss preventionists are unaware of how to address their needs.…”
Section: Hearing-impaired Workers An Estimated 19 Million Adults In Tmentioning
confidence: 99%